Study of Dibasic Elements in Indian Soybeans and Their Association with Density and Shape of Seed - Mandlik, Ashish (Asian Journal of Chemistry, 2016)
The total mineral, calcium and magnesium contents were analyzed in some Indian soybean variety seeds, collected from four different locations. The seed density and sphearicity (i.e., roundness or shape) were also analyzed to ascertain their association with metal elements. It was observed that the planting location makes statistically significant effect on total ash, calcium and magnesium contents of soybean seeds whereas the varietal variation has significant effect only on total ash. The correlation analysis of these parameters with seed density indicates negative association of seed density, total ash, calcium and magnesium whereas the sphericity has significant association only with total ash.